IDENTIFICATION AND CULTIVATION OF MEDICINAL PLANTS MENTIONED IN AYURVEDIC CLASSICS* - Mooss, N. S. (Medknow Publications & Media Pvt Ltd, 1982)
The author deals with some of the general aspects of the identifcation and cultivation of medicinal plants as well as the collection and preservation of their raw products mentioned in ancient classical Ayurvedic texts